Information sharing, bank penetration and tax evasion in emerging markets - Duc Hong Vo; Ha Nguyen; Tan Manh Vo; Michael McAleer (Risks, 2020)
Tax evasion, which is typically considered an illegal activity, is a critical problem and is considered a barrier to economic growth. A review of the literature shows that tax and social security contributions, regulations, public sector services, the quality of institutions and tax compliance, play important roles in determining the degree to which firms attempt to evade taxes. Measuring tax evasion is problematic due to data requirements and inadequacies. Few tax evasion indices have been estimated but it appears that they cannot be used for international comparisons across countries. This important issue has largely been ignored in the literature, in particular for emerging markets. Consequently, this paper is conducted to develop a new tax evasion index (TEI) using the most substantial and recent data from the standardized World Bank Enterprises Survey 2006-2017. In addition, using the newly developed TEI, the paper examines the importance and contribution of information sharing and bank penetration to the degree of tax evasion in emerging markets. The paper uses a sample of 112 emerging markets from 2006-2017 and the Tobit model in estimation. The empirical findings from the paper indicate that the average TEI during the 2006-2017 period for emerging markets is 0.62, with a range of (0.25, 0.75). In addition, we find that information sharing and bank penetration negatively affect the degree of tax evasion, as proxied by the TEI, in emerging markets. The empirical results also confirm the view that large firms are considered to have adopted good tax compliance practices, while firms located in remote areas are more likely to evade taxes. Policy implications have emerged on the basis of the empirical findings from the paper.
Keywords: 330; bank penetration; emerging markets; firms’ location; firms’ size; information sharing; tax evasion